Cyanobacterial Production of Biopharmaceutical and Biotherapeutic Proteins - Betterle, Nico; Hidalgo Martinez, Diego; Melis, Anastasios (Frontiers in Plant Science, 2020)
Efforts to express human therapeutic proteins in photosynthetic organisms have been described in the literature. Regarding microalgae, most of the research entailed a heterologous transformation of the chloroplast, but transformant cells failed to accumulate the desired recombinant proteins in high quantity. The present work provides methods and DNA construct formulations for over-expressing in photosynthetic cyanobacteria, at the protein level, human-origin bio-pharmaceutical and bio-therapeutic proteins. Proof-of-concept evidence is provided for the design and reduction to practice of “fusion constructs as protein overexpression vectors” for the generation of the bio-therapeutic protein interferon alpha-2 (IFN). IFN is a member of the Type I interferon cytokine family, well-known for its antiviral and anti-proliferative functions. Fusion construct formulations enabled accumulation of IFN up to 12% of total cellular protein in soluble form. In addition, the work reports on the isolation and purification of the fusion IFN protein and preliminary verification of its antiviral activity. Combining the expression and purification protocols developed here, it is possible to produce fairly large quantities of interferon in these photosynthetic microorganisms, generated from sunlight, CO2, and H2O.